Hubungan Penggunaan Sepatu High Heels Dan Lama Berdiri Terhadap Kejadian Hallux Valgus Pada Pegawai Badan Keuangan Dan Aset Daerah - Dinda Siratun Islam; Henry Pebruanto; Muhammad Ashhabul Kahfi Mahtar; Audi Hidayatullah Syahbani (Fakultas Ilmu Kesehatan Universitas Gresik, 2023)
Hallux valgus (HV) or what is known as a bunion or stiff big toe is a deformity of the first toe or big toe. This condition occurs when the first metatarsal deviates medially and the big toe deviates laterally with rotation, this condition is accompanied by or without medial widening of the soft tissue in the distal metatarsal. The causes of Hallux Valgus are multifactorial. but one of the causes of Hallux Valgus is the use of high heels and long standing. The purpose of this research is to find out whether there is a relationship between the use of high heels and standing time on the Hallux Valgus event in employees of the Regional Financial and Asset Management Agency in Sumbawa Regency. Type of this research is cross-sectional research is a type of research that emphasizes the time of measurement or observation of independent and dependent variable data, where variable measurements are carried out using a ruler and the Manchester scale. Test results of a total of 30 respondents, 17 respondents (56.7%) had hallux valgus and 13 respondents (43.3%) did not experience hallux valgus. Respondents with high heels ≥ 3 cm were 23 people (76.7%) and respondents with non high heels < 3 cm were 7 people (23.3%) then respondents with long standing ≥4 hours were 14 people (46.7 %) and respondents with a long standing <4 hours were 16 people (53.3%). There is a significant relationship between the height of the heel of the shoe and the incidence of Hallux Valgus and there is no significant relationship between the length of standing and the incidence of Hallux Valgus in employees of the Regional Finance and Assets Agency, Sumbawa Regency